Insight into the structure dependence on physical properties of the high temperature ceramics TaB2 boride. (July 2020) - Mai, Ziyi; Zhang, Xudong; Liu, Yiting; Yu, Hui; Wang, Feng
Abstract: The first-principles method is used to investigate the structural stabilities stability, elastic properties, elastic anisotropy, electronic properties and thermodynamics properties for TaB2 boride with six possible structures. The structure types include AlB2 -type, MoB2 -type, OsB2 -type, ReB2 -type, RuB2 -type, and WB2 -type, respectively. All structure types for TaB2 boride at ground states are thermodynamic stability due to the negative formation enthalpies. No imaginary phonon frequencies demonstrate that the six considered structures are dynamically stable. The elastic parameters indicate that TaB2 boride with six considered structures exhibits the brittle behavior. ReB2 -type, OsB2 -type and MoB2 -type TaB2 obviously exhibit the higher hardness than AlB2 -type TaB2 . ReB2 -type TaB2 boride is recommended as the potential super-hard material with the highest hardness (transcending 40 GPa). The anisotropic parameters, construction surfaces and the projection curves of Young's modulus indicate that the sequence of anisotropy is: RuB2 -type > ReB2 -type > AlB2 -type > WB2 -type > MoB2 -type > OsB2 -type. The electronic properties explain the mechanism for mechanical properties. The thermodynamic properties confirm that six types TaB2 possess the thermal stability with the elevated temperatures. Highlights: The physical properties of TaB2 are studied for six structural types. The results confirm that six different structures exhibit the structural stability. ReB2 -type TaB2 boride is recommended as the potential superhard material.